2002
DOI: 10.1046/j.1440-1681.2002.03598.x
|View full text |Cite
|
Sign up to set email alerts
|

Uneven Changes In Circulating Blood Cell Counts With Adrenergic Stimulation To The Canine Spleen

Abstract: 1. Responses of splenic diameter measured by sonomicrometry to alpha- and beta-adrenoceptor stimulants were estimated together with simultaneously measured systemic arterial and splenic venous concentrations of red blood cells (RBC), white blood cells (WBC) and platelets (PLT) in anaesthetized dogs. 2. Intravenous and intrasplenic arterial injections of adrenaline, noradrenaline and phenylephrine all produced profound decreases in splenic diameter. Increases in systemic arterial concentrations of RBC produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
(49 reference statements)
0
14
1
Order By: Relevance
“…Schaffner, Augustiny, Otto, and Fehr (1985) measured spleen size sonographically; the effects of adrenaline on granulocyte counts correlated highly with splenic contraction, but not with spleen size. In dogs, Ojiri et al (2002) reported that the lymphocytic effect of adrenaline was abolished by isolating the spleen from the rest of the circulation. Frey (1914a) further observed that splenectomised rabbits no longer showed a catecholamineinduced lymphocytosis, and the same was true of human participants (Nielsen et al, 1997).…”
Section: Immunological Significance Of the Spleenmentioning
confidence: 99%
“…Schaffner, Augustiny, Otto, and Fehr (1985) measured spleen size sonographically; the effects of adrenaline on granulocyte counts correlated highly with splenic contraction, but not with spleen size. In dogs, Ojiri et al (2002) reported that the lymphocytic effect of adrenaline was abolished by isolating the spleen from the rest of the circulation. Frey (1914a) further observed that splenectomised rabbits no longer showed a catecholamineinduced lymphocytosis, and the same was true of human participants (Nielsen et al, 1997).…”
Section: Immunological Significance Of the Spleenmentioning
confidence: 99%
“…However, investigators are still confronted with considerable variability in the canine cardiovascular shock response, since the canine spleen acts as a blood reservoir and contracts during hemorrhage, expelling red cells, thus increasing hematocrit, circulating blood volume, left ventricular preload, cardiac output and arterial O 2 content [5][6][7], which dramatically enhances the canine cardiovascular stress response [6,8]. Canine splenic contraction is mediated by endothelin and by norepinephrine via · 1 -adrenoceptors [9].…”
Section: Introductionmentioning
confidence: 99%
“…This data suggested that the spleen did not have an important role in regulation of platelet concentration, at least in response to breath-hold stimulation, despite changes in spleen size. Ojiri et al [67] came to the same conclusion by analyzing changes in circulating blood cell counts with adrenergic stimulation of the canine spleen.…”
Section: Fainting During Breath-holdmentioning
confidence: 74%